2009
DOI: 10.1007/s10549-009-0668-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the relationship between circulating tumour cells number and prognosis of metastatic breast cancer

Abstract: Modeling the relationship between circulating tumour cells number and prognosis of metastatic breast cancer. Breast Cancer Research and Treatment, Springer Verlag, 2009, 122 (1), pp.211-217. <10.1007/s10549-009-0668-7>. EPIDEMIOLOGYModeling the relationship between circulating tumour cells number and prognosis of metastatic breast cancer Abstract Circulating tumor cell (CTC) count has been shown to be an independent predictor of progression in metastatic breast, prostate, and colorectal cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 29 publications
3
52
2
Order By: Relevance
“…It was recommended that more than a single cut-off point for positivity of CTC should be used for better risk classification especially in adjuvant trials because there has been no defined threshold point for CTC positivity in this group (Tibbe et al, 2007). It was reported that as CTC levels increased as a continous variable, there was a non linear risk of death in a study of 80 metastatic breast cancer patients (Botteri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was recommended that more than a single cut-off point for positivity of CTC should be used for better risk classification especially in adjuvant trials because there has been no defined threshold point for CTC positivity in this group (Tibbe et al, 2007). It was reported that as CTC levels increased as a continous variable, there was a non linear risk of death in a study of 80 metastatic breast cancer patients (Botteri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the current article by Botteri et al [1] CTCs were determined in 80 metastatic breast cancer patients by the CellSearch TM assay. Four categories of CTC values (0 cells, 1-4 cells, 5-20 cells and more than 20 cells) were defined and then related to progression-free and overall survival.…”
Section: To Cite This Versionmentioning
confidence: 99%
“…Fifty to 80% of metastatic patients have circulating tumor cells in the blood circulation [1][2][3]. The most currently used approach for CTC detection is the CellSearch TM system which is an semiautomated device based on immunofluorescence and flow cytometry.…”
Section: To Cite This Versionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Various studies have demonstrated the presence of CTCs in peripheral blood of patients and their association with tumor progression and metastatic development. [5][6][7] Reports have also shown that a change in CTCs number predicts response to therapy and can evaluate residual disease.…”
Section: Introductionmentioning
confidence: 99%